An International Economy with Country-Specific Money and Productivity Growth Processes - Nicholas Ricketts; Thomas H. McCurdy (Queen's University, Department of Economics, 1991)
This paper analyses a stochastic international growth model with money and country-specific forcing processes for productivity and money growth rates. Monies are required due to cash-in-advance constraints for consumption goods but the liquidity constraints need not be binding for all periods. An individual can trade claims on future currency units for both countries through government bond markets. Each country specializes in the production of one of the goods but individual agents can invest, subject to installation costs, in any available technology. Two versions of the model are simulated in order to compare different degrees of international mobility of physical capital. The moments of the forcing processes are calibrated to a sample of U.S. and Canadian data. A perfectly pooled equilibrium solution is computed numerically, using the Marcet method of parameterized expectations and the moments of the endogenous variables are compared to those for the actual data. The interdependence implied by the model is illustrated by a series of impulse responses. Particular attention is focused on the implications of capital mobility, the asymmetry of the forcing processes across countries, the implications of the liquidity constraints, and the interaction between the real and nominal components of the model. For example, with endogenous production, we find that monetary fluctuations cause business cycle behavior in consumption and investment while the effect on goods and asset prices can be substantially different from that in endowment models. We also find that the effects of monetary policy are transmitted to other countries via exchange rate and terms of trade adjustments.
Keywords: 330